Isu Perpanjangan Masa Jabatan Presiden Tiga Periode di Media Massa terhadap Sikap Publik - Radita Gora; Aladdin, Yuri Alfrin (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The issue of extending the President's term of office to three terms has become very strong along with the issue of postponing the 2024 Election circulating in the community, which has then invited controversy in society and also massive coverage in the mass media, including hot discussions on social media. The media has a big role to influence public attitudes. So, through the Inoculation theory, we attempt to examine explanatively the issue of extending the presidential term of office in the media on public attitudes using a quantitative approach. Based on the research results, it shows that there is an influence between the issue of extending the President's term of office and postponing the 2024 Election on public attitudes which show disapproval of these two issues. The public believes that extending the presidential term of office and postponing elections is a violation of the constitution and also creates a sense of distrust among respondents towards the current government. Apart from that, respondents also linked the two issues circulating in the mass media and online media to the interests of IKN and also considered that the government was not functioning well in accordance with the mandate of the constitution.